The Influence of Company Size, Solvency, Profitability and Leverage on Audit Delay in Food and Beverage Sector Manufacturing Companies In 2019–2022 - Elisa Y Nainggolan; Enda Noviyanti Simorangkir; Alincia Tabitha Sormin; Sekar Nauli Andrita Ningrum; Fhikry Ahmad Halomoan Siregar (Lafadz Jaya Publisher, 2024)
This study aims to examine whether the effect of company size, solvency, profitability and leverage on audit delay in food and beverage companies listed on the Indonesia Stock Exchange. Indonesia Stock Exchange (IDX) is a stock exchange that operates in Indonesia. The Indonesia Stock Exchange is the result of the merger of the Jakarta Stock Exchange (BEJ) and the Surabaya Stock Exchange (BES). For operational and transaction effectiveness, the Government decided to merge the Jakarta Stock Exchange as a stock market with the Surabaya Stock Exchange as a bond and derivatives market into the IDX. The merged exchange began operations on December 1, 2007. This study uses an associative approach which aims to analyze the relationship between one variable and another or how a variable affects another variable. The number of samples analyzed was 19 company samples with sample determination using purposive sampling. Research data using SPSS 20 with descriptive statistical analysis, normality test, histogram graph, multicollinearity test, heterocollinearity test, autocollinearity test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results showed that company size has no influence on audit delay in food and beverage sector manufacturing companies listed on the IDX for the 2019-2022 period. Solvency has no effect on audit delay in food and beverage sector manufacturing companies listed on the IDX for the 2019-2022 period. Profitability has an effect on audit delay in food and beverage sector manufacturing companies listed on the IDX for the 2019-2022 period. Leverage affects audit delay in food and beverage sector manufacturing companies listed on the IDX for the 2019-2022 period. From the research conducted, it is concluded that company size, solvency, profitability, and leverage simultaneously affect audit delay in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period.